Integrating Environmental Ethics into Christian Religious Education: An Analytical and Interpretive Approach through Project-Based Learning - Imelda Butarbutar; Riana Lumban raja; Sorta Sihombing; Sartika Maria Siregar; Tomi Jonatan Simbolon (Ilmu Inovasi Nusantara, 2025)
This study explores the integration of environmental ethics into Christian Religious Education (CRE) using an analytical and interpretive approach. The core problem addressed in this research is the increasing neglect of ecological responsibility among communities, particularly within the context of religious learning, amid the challenges of globalization and industrialization. These dynamics often reduce the emphasis on moral, ethical, and environmental awareness, creating an urgent need to realign faith-based education with environmental stewardship. The main objective of this study is to uncover how CRE can serve as a foundational platform for shaping students' ethical and moral values that are environmentally conscious. By embedding ecological values in religious learning, the study aims to foster a more holistic formation of character that emphasizes the responsibility to care for creation. This research employs project-based learning as a methodological framework, wherein students engage in real-world learning activities that connect theological principles with environmental ethics. Through analytical and interpretive methods, the study examines how these educational experiences impact students’ perceptions, behaviors, and ethical reflections on nature and sustainability. The findings reveal that integrating environmental ethics within CRE significantly enhances students' awareness of ecological issues and their role as stewards of the environment. It also encourages community-level reflections and actions grounded in Christian teachings. The implication of this research is the potential for faith-based education, particularly in churches and Christian communities, to become a transformative force in promoting ecological responsibility. By aligning religious values with sustainable practices, CRE can contribute to broader efforts in cultivating environmental ethics across generations